Pemberdayaan Ekonomi Masyarakat Melalui Pembuatan Kripik Singkong Aneka Rasa di Dukuh Wonorejo Desa Bedrug - Winarti Winarti; Teguh Ansori (Institut Agama Islam Sunan Giri Ponorogo, 2023)
Dukuh Wonorejo, Bedrug Village, is located in Pulung District, Ponorogo Regency. Most of the population work as farmers and dairy farmers. Dukuh Wonorejo has a lot of land that can be used as a means of agriculture and the community's economy which often generates income and even becomes the main occupation of the community, one of which is cassava. The results of planting cassava have not been able to meet daily needs because the price is always relatively cheap. Therefore there needs to be innovation regarding cassava processing so that it has a high selling price. The purpose of this community activity is to increase the economic value of cassava into cassava chips with various flavors. The service method used is Asset Based Community Development (ABCD) involving housewives in Wonorejo hamlet, Bedrug village, Pulung sub-district, Ponorogo district. Some people in the Wonorejo hamlet empower cassava agricultural products to become processed chips with a variety of flavors. The results obtained by the community are cassava chips which already have a crunchy taste and also have spicy and sweet flavors. The existence of cassava chip processing from the community is expected to improve the economy and community skills sothat it can have an impact on high buyer interest.